Synthesis and Dimerization Properties of Cup‐ and Bowl‐shaped Cyclic Trilactams. Issue 6 (6th May 2020) - Sartyoungkul, Sitanan; Yakiyama, Yumi; Sakurai, Hidehiro
Abstract: Two chiral trilactams, cup‐shaped (−)‐1 and bowl‐shaped (−)‐2, were synthesized. Single crystal X‐ray analysis revealed that (−)‐1 formed dimer structure by the formation of three NH⋅⋅⋅O type complementary hydrogen bonds at three amide moieties. The equilibrium constant ( K eq ) and kinetic parameters ▵ H ° and ▵ S ° of the dimer formation phenomenon of (−)‐1 were determined by variable temperature proton NMR. Further binding energy calculation on both (−)‐1 and (−)‐2 dimers confirmed the more favourable formation of (−)‐1 dimer than (−)‐2 dimer, explaining the significant solubility difference of the two against the less polar solvent, such as CHCl3 . Trilactam (−)‐1 afforded coordination polymer by complexation with Zn 2+, keeping the capsule‐like structure. Abstract : Three dimensional structures tailored with a hydrogen‐bonded component are highly useful building blocks for non‐covalent framework constructions. Here we report the synthesis and structural properties of two novel chiral cup‐ and bowl‐shaped cyclic trilactams. X‐ray crystal analysis revealed the dimeric capsule‐like structure of cup‐shaped trilactam by three self‐complementary NH⋅⋅⋅O type intermolecular hydrogen bonds. The favorable dimerization of the cup‐shaped over the bowl‐shaped trilactam was intensively studied by variable temperature proton NMR and DFT calculation, which confirmed to the solubility variation against the less polar solvent. The unique structural cup‐shaped dimer was utilized in metal coordination to construct the networking polymer.